Measurement of Partial Discharge Induced Electromagnetic Wave using Loop Antenna - Umar Khayam; Fendi Imam Fatoni (Proceeding of the Electrical Engineering Computer Science and Informatics, 2017)
Partial discharge (PD) detection by detecting    the released   energy   in the form   of   electromagnetic (EM)   wave during discharge using Ultra-High Frequency (UHF) antenna is one of the methods to determine insulation system quality of power apparatus. The main advantage of UHF PD detection system by using antenna are the capability to detect PD signal without firstly shut down the power apparatus. Therefore, the PD measurement system based on EM wave induced by PD detected by the sensor is needed. First, the sensors which be able to detect PD induced EM wave in ultra wide band need to be designed and manufactured. Second, the characteristics of PD induced EM wave measured by the sensors need to be investigated. This paper deals with measurement of PD induced EM wave by using loop antenna. The results show that the further the distance of loop antenna to PD source is, the lower Vpp is. This is due to EM wave attenuation. At the distance 225 cm from PD source, Vpp of PD is equal to Vpp of the background noise (BGN). Therefore, the maximum distance of the loop sensor to PD source is 225 cm.